ALIRAN-ALIRAN DALAM AGAMA YAHUDI - Andika Andika (Abrahamic Religions: Jurnal Studi Agama-Agama, 2022)
Judaism is a part of the Abrahamic religion. Abrahamic religions in their development, such as Judaism experienced divisions, giving rise to new schools of Judaism. New schools of Judaism emerged due to differences in views and opinions among the Jews. This study aims to determine the definition of sects in Judaism along with the emergence factors of each sect in Judaism. Some of the schools in Judaism are beginning with Enlightenment Judaism, Reform Judaism, Orthodox Judaism, Conservative Judaism, and Reconstructionist Judaism. Apart from these sects, Judaism is further divided into several sects, including the paris, saduki, readers, writers, essenes, and fanatics or zealots. Among the schools in Judaism, not only differ in terms of background but also in terms of understanding of the teachings in Judaism. Therefore, it is undeniable that there are differences in religious understanding and practice in Judaism in each sect. This study uses a descriptive method through a qualitative approach with literature study. The result of the discussion in this study is to know the definitions, factors, and schools of Judaism. And this study concludes that the Jewish religion in its development has various kinds of flow